Nursing care for diabetic toe ulcers: A case series report and literature review - Li Ji; Jiao-jiao Bai; Jiao Sun; Zheng Wang (Elsevier, 2016)
This paper reports the treatment of eight cases with toe ulcers. The eight patients received nursing treatments, including debridement, dressings, decompression, anti-fungal management, and education from specialist nurses. The patients were also given drugs to control glucose, nourish the nerve, and improve blood circulation of the lower extremities. The toe ulcers of the eight diabetic patients healed after 42-168 days [average 85 ± 36 days]. Thus far, few studies have focused on diabetic toe ulcers. Timely identification of risk factors and regular toe care could decrease the prevalence of toe ulcers and shorten the recovery time in patients with diabetic mellitus. Hence, these patients must be diagnosis and treated early. Results suggest that feet, particularly toes, should be inspected and cared for regularly in diabetic patients.